1978
DOI: 10.1073/pnas.75.9.4544
|View full text |Cite
|
Sign up to set email alerts
|

Isolated microvessels: the blood-brain barrier in vitro.

Abstract: Isolated bovine retinal and brain microvessels, exhibiting a patent lumen, were used to study the contribution of the microvasculature to the blood-brain and blood-retina barriers. The diffusion marker, sucrose, was taken up slowly by the isolated microvessels in contrast to leucine, tyrosine, and valine which were taken up at a considerably faster rate. Uptake of leucine was temperature dependent but resistant to inhibition by ouabain and sodium azide. The large neutral amino acids exhibited stereospecificity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 37 publications
5
36
0
Order By: Relevance
“…However, other investigators have shown that isolated brain microvessels demonstrate linear rates of glucose oxidation for at least 90 min of incubation, 9 actively transport potassium, 9 have almost identical amino acid transport K m values as that observed in vivo, 10 and have high affinity catecholamine receptors. 11 Therefore, while the "metabolic viability" of the brain microvessel isolated by mechanical homogenization techniques is uncertain, this preparation maintains many cellular functions of the brain capillary that can be investigated in vitro.…”
Section: Methodsmentioning
confidence: 88%
“…However, other investigators have shown that isolated brain microvessels demonstrate linear rates of glucose oxidation for at least 90 min of incubation, 9 actively transport potassium, 9 have almost identical amino acid transport K m values as that observed in vivo, 10 and have high affinity catecholamine receptors. 11 Therefore, while the "metabolic viability" of the brain microvessel isolated by mechanical homogenization techniques is uncertain, this preparation maintains many cellular functions of the brain capillary that can be investigated in vitro.…”
Section: Methodsmentioning
confidence: 88%
“…(x60.) the brain capillaries are patent at both ends (30) and, thus, both the lumenal and antilumenal membranes are available for uptake in the in vitro studies, there is an approximately 1-to 2-min lag for molecular diffusion into the lumen of the microvessel. Therefore, the rapid binding within 5 sec of incubation suggests that enhanced binding also takes place at the antilumenal membrane of the capillary.…”
Section: Discussionmentioning
confidence: 99%
“…IEF was performed at 30 W, at a maximum voltage of 3000 V, and was performed for a duration of 4000 V-hr at 10°C. The IEF gels were fixed with 10% trichloroacetic acid (TCA) and 5% sulfosalicylic acid at room temperature for 60 min, washed in 30%o methanol/10%6 acetic acid for 30 (20) and as described (21). The native and cationized IgG molecules were iodinated to a specific activity of 3 ,Ci/,g (1 Ci = 37 GBq) with 1251 and Abbreviations: BBB, blood-brain barrier; TCA, trichloroacetic acid.…”
mentioning
confidence: 99%
“…Recent experimentation in this and other laboratories led to the development of isolation procedures that permit the harvest of popula tions of morphologically intact blood vessels from whole brain and isolated brain regions Jarrott et al, 1979;Orlowski et al, 1974;Hjelle et al, 1978). In the present study we have employed highly sensitive radioenzymatic procedures for the detection and quantification of norepinephrine (NE), epinephrine (EP), dopamine (DA) and histamine in cerebral microvessels obtained from either rat, rabbit or bovine brain tissue.…”
Section: Introductionmentioning
confidence: 99%